Role of Strength Training on Poststroke Hemiparesis, a Review on Recent Developments (Bangladesh Journal of Neuroscience, 2013)
Stroke is the leading cause of activity limitation and participation restriction all over the world and weakness presents a more serious compromise to movement and function in poststroke hemiplegia than spasticity. In this article we have gone through publications on functional consequences of post-stroke paresis and effect of resistance training in effective stroke rehabilitation and reviewed the clinical and functional phenomena of paresis in stroke survivors, effects of high-resistance training on improvement of strength and functional capacity. By examining the various facets of weakness, we can understand the specific nature of motor impairment and can identify potential strategies to mitigate its effects, functional improvement and participation in activities. The specific aims were to emphasis the importance of strength training in the functional improvement of patients suffering from stroke with paralysis.Bangladesh Journal of Neuroscience 2013; Vol. 29 (2) : 124-129